WEB-BASED COMPUTER BASED TEST(CBT) APPLICATION DESIGN - Rahmat Dinur; Elfrida Chris Damayanti (INFOKUM, 2019)
Computer Based Test or abbreviated as CBT is a test that is carried out using computers and the internet, the characteristics of this system are almost the same as tests in general, only the media for the work are different. The difference lies in the delivery of the problem that no longer uses paper and the correction can be done immediately after the test is complete, thus providing convenience for all users. The design of this system is carried out with a modeling language using UML, while the programming used is PHP and MySQL. From the results of this design, the resulting Computer Based Test information system is expected to make it easier for teachers and students in the teaching process, especially in conducting UAS and UTS school exams, as well as training students so that they can face online- based exams given by the government.